"Let Our Ballots Secure What Our Bullets Have Won": Union Veterans and the Making of Radical Reconstruction. Issue 4 (29th November 2022) - WEAVER, MICHAEL
Abstract : After the Civil War, congressional Republicans used sweeping powers to expand and enforce civil rights for African Americans. Though the electoral benefits of African American suffrage were clear, Republicans had to overcome party divisions and racist voters. This paper argues that the war imbued Northern veterans with the belief that true victory required renewing the Union by abolishing slavery and establishing (imperfect) legal equality. This made veterans more receptive to Radical Reconstruction and ignited activism for it from below. Using difference-in-differences, I show that greater enlistment increased Republican vote share, particularly in pivotal postwar elections. Moreover, "as-if" random exposure to combat deaths increased Republican partisanship among soldiers after the war. Finally, I show that veterans became more likely to vote for African American suffrage. The paper concludes that Union veterans, through their votes and their activism, were a decisive part of the white coalition that backed America's "Second Revolution."